2022
DOI: 10.1097/pgp.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Evaluation of CTNNB1 Mutations in High-Intermediate Risk Endometrial Endometrioid Carcinoma

Abstract: CTNNB1 mutations convey increased risk of recurrence in low-risk endometrial endometrioid carcinoma (EEC). Results from previous high-intermediate risk (HIR) cohorts are mixed. The aims of this study were to correlate CTNNB1 mutational status with clinical outcomes and to evaluate the relationship between CTNNB1 mutations and the 4 prognostic subgroups defined by The Cancer Genome Atlas in HIR EEC. CTNNB1 mutational status was determined by Sanger sequencing of exon 3 of the CTNNB1 gene. Mismatch repair, POLE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Table 4 displays the rates of mutations per subgroup (displayed as percentage of cases with a mutation in the gene) in a subset of the genes analyzed by the NGS panel. As expected based on previous reports, CTNNB1 mutations were most prevalent in the NSMP subgroup (P < 0.0005 vs MMRd, P < 0.001 vs p53abn, P = 0.7183 vs POLE [likely due to low n in POLE subgroup] by Fisher's exact test) (6,32,33). All detected CTNNB1 mutations were at known oncogenic or likely oncogenic hotspots (as determined by OncoKB [oncokb.org]) with the exception of 2 in-frame deletions of unknown significance (I35_H36del and Y30_S33del) that are in the same region as known activating point mutations.…”
Section: Additional Findings Derived From Next-generation Sequencing-...supporting
confidence: 87%
“…Table 4 displays the rates of mutations per subgroup (displayed as percentage of cases with a mutation in the gene) in a subset of the genes analyzed by the NGS panel. As expected based on previous reports, CTNNB1 mutations were most prevalent in the NSMP subgroup (P < 0.0005 vs MMRd, P < 0.001 vs p53abn, P = 0.7183 vs POLE [likely due to low n in POLE subgroup] by Fisher's exact test) (6,32,33). All detected CTNNB1 mutations were at known oncogenic or likely oncogenic hotspots (as determined by OncoKB [oncokb.org]) with the exception of 2 in-frame deletions of unknown significance (I35_H36del and Y30_S33del) that are in the same region as known activating point mutations.…”
Section: Additional Findings Derived From Next-generation Sequencing-...supporting
confidence: 87%
“…Interestingly, despite otherwise favorable clinicopathologic features, CTNNB1 mutations in predominantly early-stage and low-grade NSMP endometrial carcinomas have been reported as a poor prognostic marker associated with decreased recurrence-free survival 8,11–15 . Although these data include a subset of cases of CHEC, 1,2 it should be noted that some studies have not confirmed the prognostic significance of aberrant beta-catenin 10,16,17 . Abnormal nuclear beta-catenin expression has been described in almost all reported cases of CHEC 2–4 .…”
Section: Discussionmentioning
confidence: 98%
“…Beta-catenin immunohistochemistry is generally considered to be a reliable surrogate for CTNNB1 exon 3 activating mutation, with sensitivity ranging from 85% to 91% and specificity ranging from 82% to 100%, depending on the study parameters, specific mutation, and beta-catenin antibody clone. [8][9][10] Interestingly, despite otherwise favorable clinicopathologic features, CTNNB1 mutations in predominantly early-stage and low-grade NSMP endometrial carcinomas have been reported as a poor prognostic marker associated with decreased recurrence-free survival. 8,[11][12][13][14][15] Although these data include a subset of cases of CHEC, 1,2 it should be noted that some studies have not confirmed the prognostic significance of aberrant beta-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations